Low temperature synthesis of metal doped perovskites catalyst for hydrogen production by autothermal reforming of methane. (7th September 2016) - Chen, Li; Pradhan, Sivaram
Abstract: Platinum and rhodium doped CeAlO3 perovskites catalysts have been synthesized by adopting citric acid method at much lower temperature than the high temperature traditional solid state route. Systematic characterization of the precursors at various stages was attempted by XRD, BET, XPS, TEM and SEM-EDS analyses to confirm the structure and properties of the perovskites. These catalysts were evaluated in autothermal reforming of methane for hydrogen production. The results showed that the CH4 conversion was 99% at 650 °C which enhanced after the incorporation of Pt in Rh doped CeAlO3 perovskites. Compared to monometallic Rh catalysts, RhPt bimetallic catalysts exhibit superior catalytic performance in the methane steam reforming due to synergetic effect. The noble metals such as Pt and Rh are stabilized in its ionic form as they are locked in the structure (preventing sintering of metal particles and catalyst deactivation), thus yielding highly stable catalysts under highly reducing conditions. Graphical abstract: Highlights: Nobel metal perovskites successfully synthesized at low temperature. Citrate method produce pure CeAlO3 . Modified perovskites are highly active for hydrogen production in ATR. RhPt bimetallic catalyst exhibits superior catalytic activity. Catalyst shows stability more than 60 h in time on stream.